The Concept of Personality and Its Relevance to Character Education in The Light of The Islamic Worldview - Alim, Akhmad; Patahuddin, Askar; Hamka, Syamsuar; Amirullah, M. (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aims to describe the concept of personality and education in the Qur'an and its relevance to character education. This research is qualitative descriptive research through literature study and content analysis methods. The results show that the concept of personality in the Qur'an can be categorized in many forms, but can be categorized into five personal points with the spirit of mu'min, muá¹£liá¸¥, mujÄhid, muta'Äwin, and mutqin. The concept of character education in the Qur'an can be formulated in the form of a balanced remembrance and thought, consistently carrying out worship, leaving the bad, and carrying out all forms of goodness. The relevance of personality to character education can be seen from efforts to educate the soul to become a believer who has an attitude of faith above a straight faith, worships according to instructions, and has a noble character. As for the soul of a muá¹£liá¸¥, mujÄhid, muta'Äwin, and mutqin, it can be seen from the effort to continue learning to teach science, preaching by preventing the bad and inviting the good, as well as patience, cooperation (gotong royong), striving for the best (professionalism), of every trust given. The application of character education based on the personality of the Qur'an with the Islamic Worldview is an effort to view everything based on faith in Allah, faith in revelation, faith in the Prophet, and so on.